Proposal of re-ring distribution system at MARA Institute of Technology ( ITM ) Shah Alam / Syaiful Bahri Ismail - Ismail, Syaiful Bahri (1992)
A study of an existing distribution system and alternative ring system arrangement at ITM has been made. In this proposal, the high tension underground cable networks have also been suggested namely the ring main circuit and duplicate ring circuit. The quantities of current rating, voltage drop, cable sizes, short circuit rating and estimating of 11 KV cables were calculated. Comparison between the two ring circuit arrangements is also included in the last chapter.